2021
DOI: 10.48550/arxiv.2109.12536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A minimal non-supersymmetric $E_6$ Grand Unified Theory without intermediate symmetry

Chandini Dash,
Snigdha Mishra,
Sudhanwa Patra
et al.

Abstract: We consider a minimal renormalizable non-supersymmetric E6 Grand Unified Theory using only fundamental representation 27 for fermions and scalars. The proposed model, guided by TeVscale vector-like fermions and scalars offer successful gauge unification even in the absence of any intermediate symmetry. Embedded with threshold corrections, it is shown to be compatible with the present experimental limit on proton decay lifetime. The unique feature of the model shows that, the GUT threshold corrections to the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In the central plots, we illustrate regions that satisfy the electron MDM constraints for Cs and Rb, to within one-sigma. For the muon sector in Figures 5(c) and 6(c), we show contours representing the benchmark values of ξ 23 , consistent with the sign preference for each model -as per equations ( 46) and (47).…”
Section: E Summary Of Additional Constraintssupporting
confidence: 55%
“…In the central plots, we illustrate regions that satisfy the electron MDM constraints for Cs and Rb, to within one-sigma. For the muon sector in Figures 5(c) and 6(c), we show contours representing the benchmark values of ξ 23 , consistent with the sign preference for each model -as per equations ( 46) and (47).…”
Section: E Summary Of Additional Constraintssupporting
confidence: 55%
“…In the context of GUT, the popular models are SU(5) [41], SO (10) [18, [42][43][44][45][46][47][48][49][50][51][52]] and E 6 [53][54][55][56][57][58][59][60][61], where many of the unsolved issues of the SM can be addressed. In most of the literature, it is found that all GUTs without any intermediate symmetry breaking and in the absence of supersymmetry, fails to unify the gauge couplings corresponding to three fundamental forces as described by SM.…”
Section: Introductionmentioning
confidence: 99%